About the acceleration rate of relativistic beams by a surface wave in a dielectric laser accelerator - Bolshov, O.O.; Vasiliev, A.V.; Povrozin, A.I.; Sotnikov, G.V. (Вопросы атомной науки и техники, 2021)
An analysis of the dependence of the acceleration rate of charged particles by a surface wave arising when a laser pulse/(plane wave) is incident on the interface between two dielectric media on the phase velocity of the excited wave is carried out. It is shown that at resonance acceleration this dependence has a maximum, for ultra-relativistic particles the acceleration rate tends to zero. The dependences of the acceleration rate on the phase velocity of the excited wave for various refractive indices (dielectric permittivities) of optically transparent medias are investigated analytically and numerically. Проведено аналіз залежності темпу прискорення заряджених частинок поверхневої хвилею, що виникає при падінні лазерного імпульсу/(плоскої хвилі) на межу розділу двох середовищ, від фазової швидкості хвилі, що збуджується. Показано, що при резонансному прискоренні ця залежність має максимум, для ультрарелятивістських частинок темп прискорення прагне до нуля. Аналітично та чисельно досліджено залежності темпу прискорення від фазової швидкості хвилі, що збуджується, для різних показників заломлення (діелектричної проникності) оптично прозорих матеріалів. Проведен анализ зависимости темпа ускорения заряженных частиц поверхностной волной, возникающей при падении лазерного импульса/(плоской волны) на границу раздела двух сред, от фазовой скорости возбуждаемой волны. Показано, что при резонансном ускорении эта зависимость имеет максимум, для ультрарелятивистских частиц темп ускорения стремится к нулю. Аналитически и численно исследованы зависимости темпа ускорения от фазовой скорости возбуждаемой волны для различных показателей преломления (диэлектрических проницаемостей) оптически прозрачных материалов.